Android Based College Management System - Pujare, D.S; Mir, M.S; Melasagare, S.M (International Journal of Computer Sciences and Engineering, 2020)
In this paper focuses on a College Management system is an android application Based project. Which is helpful for students as well as the Faculties, Finance Department, Library and Admin (Record Manager). In the existing system all the activities are done manually. It is very costly and time consuming. In our proposed system, Student can view college related details like assignment, notes, notices, view available books details, give feedback or submit their issues etc. He/She view the detail of their Fee, etc. Librarian can record new book details also issue book and renew book, etc. Finance department can handle record like student fee details and salary of employee details, etc. Faculty can upload assignment, mark student attendance, etc. The proposed work has five modules: 1.Student 2.Faculty 3.Finance department 4.Librarian 5.Admin. In Student module student need to register after the registration He/She need to be verify their email. Only after verification of email He/She can login into system. In Librarian module, when Librarian add new book, that notification goes to all the subscriber of application access the system. In Admin module, admin can handle and view the all record which store in database. This college management system access anytime and anywhere, whenever user wants.